‘Philosophus et Mathematicus Incomparabilis’: Johannes Hudde (1628–1704), de Verlichte burgemeester van Amsterdam - de Jong, Theo; Zuidervaart, Huib (Studium, 2018)
This article is devoted to the scholarly achievements of Johannes Hudde, who in the late seventeenth century was one of the most influential mayors of Amsterdam. Already in his years as a student at Leiden University, Hudde became renowned as a very skilled mathematician. Coming from an elite Amsterdam family, it was his destiny to become a magistrate in the service of the city of Amsterdam. He also occupied the office of Director of the Dutch East India Company VOC. In these high posi- tions Hudde stimulated many technical innovations, for instance concerning the quality, quantity and supply of water in Amsterdam; the introduction of street lighting; the improvement of fire hoses and much more. His enlightened ideas also gave rise to fairly moderate points of view. Several con- troversial ideas could be published without obstruction during Hudde’s time as one of Amsterdam’s ‘Burgemeesters’.